2014
DOI: 10.1016/j.ygyno.2013.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Serum HE4 as a prognostic marker in endometrial cancer — A population based study

Abstract: These findings demonstrate the utility of serum HE4 as a prognostic biomarker in endometrial cancer in a large, population-based study. In particular they highlight the utility of HE4 for pre-operative risk stratification to identify high-risk patients within low-grade endometrioid endometrial cancer patients who might benefit from lymphadenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 25 publications
10
80
2
2
Order By: Relevance
“…[10][11][12] Besides CA125, EC also could be diagnosed by elevated levels of HE4, CA724, and CA19-9, each with their own unique advantages. [13][14][15] In our test, we detected serum level of HE4, CA125, CA724, and CA19-9 in 105 patients with EC; the results showed that the level of tumor markers was obviously higher in the EC group than that in the healthy controls. Sensitivity of HE4 in patients with EC was 58%, much higher than sensitivity of CA125, CA724, and CA19-9 (35.4%, 11.3%, and 16.3%, respectively).…”
Section: Discussionmentioning
confidence: 74%
“…[10][11][12] Besides CA125, EC also could be diagnosed by elevated levels of HE4, CA724, and CA19-9, each with their own unique advantages. [13][14][15] In our test, we detected serum level of HE4, CA125, CA724, and CA19-9 in 105 patients with EC; the results showed that the level of tumor markers was obviously higher in the EC group than that in the healthy controls. Sensitivity of HE4 in patients with EC was 58%, much higher than sensitivity of CA125, CA724, and CA19-9 (35.4%, 11.3%, and 16.3%, respectively).…”
Section: Discussionmentioning
confidence: 74%
“…In a meta-analysis, Zhen et al reported that the diagnostic accuracy of HE4 in distinguishing ovarian cancer from other benign gynecological diseases was found to be superior to that of CA125 (23). More recently, Brennan et al reported in a large population-based study that serum HE4 may be a useful prognostic biomarker in endometrial cancer (17). Furthermore, Yang et al determined its importance as a preoperative predictor for optimal tumour cytoreductive surgery in epithelial ovarian cancer (18).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported its specifity and sensitivity as an ovarian cancer biomarker (16). In 2009, the United States Food and Drug Administration (FDA) approved HE4 as a useful marker for monitoring patients with epithelial ovarian cancer (17); and in September, 2011, the FDA also approved marketing of HE4 for the detection of ovarian masses (18). There is accumulating evidence that HE4 may also be a useful marker for endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Brennan et al performed a large population-based cohort study to evaluate if serum HE4 can offer preliminary pre-operative risk stratification for EC. Specifically because of the high expression level of HE4 in EC tissue, and the increased serum level in this group of patients [28,29]. The result strongly implied that serum HE4 was an independent poor prognostic marker, and it was suggested to use HE4 serum assay as a cost-effective approach to avoid unnecessary lymphadenectomy in patients with low risk EC.…”
Section: Human Epididymis Protein 4 (He4)mentioning
confidence: 82%
“…In a different paper the expression of HE4 in EC and its relations to clinicopathological parameters and prognosis of EC was studied. The goal was to detect the expression rate of HE4, by means of immunohistochemical using streptavidin-peroxidase, in EC, endometrial atypical hyperplasia, and normal endometrial tissue samples, respectively [27,29]. The results implied that the intensity of HE4 expression increased with degree of malignancy.…”
Section: Human Epididymis Protein 4 (He4)mentioning
confidence: 99%